State-Crime Nexus on the Myanmar Border: The Symbiosis of the Political Economy of the Military Junta and Border Guard Forces in the Yatai New City Ecosystem - Dita Amanda Prastya; Honest Dody Molasy; Agung Purwanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
The 2021 military coup in Myanmar precipitated a collapse in state governance, creating a vacuum often assumed to be the primary driver of organized crime. However, the rapid expansion of Yatai New City in Myawaddy suggests a more complex dynamic. This study investigates the political economy of the Yatai New City, specifically the interaction between foreign investors, the Karen Border Guard Forces (BGF), and the Military Junta. Employing the State–Crime Nexus framework and a qualitative approach based on source triangulation, this research challenges the